Negative electrode sheet, method for manufacturing the same, and battery
Patent Information
- Application Number
- CN202510533891.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-04-25
AI Technical Summary
比如,目前极片层级改善手段之一的双层涂布收到人们越来越多的关注,双层涂布的技术手段改善了电池的快充能力,但因其将快充能力更好的负极材料置于极片上层与电解液接触,导致高温性能有所劣化
[0062]在本申请负极片中,第一活性物质的振实密度为T1,第二活性物质的振实密度为T2,第三活性物质的振实密度为T3,其中,T3>T1>T2。第三活性物质采用振实密度更高的材料,其形貌结构更加圆润,可以提高第三负极涂层的高温性能;第二活性物质采用振实密度较低的材料,可以保证负极片具有更高的快充能力;第一活性物质材料的振实密度高于第二活性物质材料的振实密度,且低于第三活性物质材料的振实密度,可以使第一负极涂层保持高容高压实的能力。本申请的负极片,通过控制三层涂层中各活性物质材料振实密度大小的关系,可以使该负极片制备的电池兼顾较为优异的快充能力和高温性能。
Smart Images

Figure BDA0005377614610000151
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and more specifically, to a negative electrode sheet, its preparation method, and a battery. Background Technology
[0002] In recent years, with the continuous development of science and technology and the economy, people's demand for high-efficiency energy storage batteries has been increasing. Lithium-ion batteries are currently the most widely used rechargeable batteries. People are increasingly demanding higher performance in terms of high-temperature and fast-charging capabilities, but the directions for improving high-temperature and fast-charging performance are generally opposite. Achieving a balance between high temperature and fast charging remains a challenge for the industry. For example, double-layer coating, one of the current methods for improving electrode layers, has received increasing attention. While double-layer coating improves the battery's fast-charging capability, placing the faster-charging negative electrode material on top of the electrode in contact with the electrolyte leads to some degradation in high-temperature performance.
[0003] Therefore, it is necessary to take effective measures to improve both the high-temperature and fast-charging performance of batteries. Summary of the Invention
[0004] In view of this, the present invention aims to at least partially solve one of the technical problems in the related art. To this end, the present invention provides a negative electrode sheet, a method for preparing the same, and a battery, which exhibits excellent high-temperature and fast-charging performance.
[0005] To solve the above-mentioned technical problems, this application is implemented as follows:
[0006] According to one aspect of this application, an embodiment of this application provides a negative electrode sheet, the negative electrode sheet comprising:
[0007] current collector;
[0008] A first negative electrode coating is disposed on at least one side surface of the current collector along the thickness direction. The first negative electrode coating includes a first active material, and the tap density of the first active material is T1.
[0009] A second negative electrode coating is disposed on the surface of the first negative electrode coating away from the current collector. The second negative electrode coating includes a second active material, the tap density of which is T2.
[0010] A third negative electrode coating is disposed on the surface of the second negative electrode coating away from the first negative electrode coating. The third negative electrode coating includes a third active material, and the tap density of the third active material is T3.
[0011] Among them, T1, T2, and T3 satisfy the following relationship:
[0012] T3 > T1 > T2.
[0013] In some of these embodiments, the tap density T1 of the first active material satisfies: 1 g / cm³ 3 ≤T1≤1.2g / cm 3 .
[0014] In some embodiments, the tap density T2 of the second active material satisfies: 0.9 g / cm³ 3 ≤T1≤1.1g / cm 3 .
[0015] In some embodiments, the tap density T3 of the third active material satisfies: T3 ≥ 1.1 g / cm³ 3 .
[0016] In some embodiments, the tap density T3 of the third active material satisfies: T3 ≥ 1.2 g / cm³ 3 .
[0017] In some of these embodiments, the rate performance of the first active substance is C1, the rate performance of the second active substance is C2, and the rate performance of the third active substance is C3.
[0018] Among them, C1, C2, and C3 satisfy the following relationship:
[0019] 0.8*C2≤C3≤C2;
[0020] C1≥0.5*C3.
[0021] In some of these embodiments, the OI value of the third active material layer is higher than that of the second active material layer.
[0022] In some of these embodiments, the OI value of the first active material layer is 20 to 30.
[0023] In some of these embodiments, the OI value of the second active material layer is 5 to 20.
[0024] In some embodiments, the OI value of the third active material layer is 15 to 25.
[0025] In some of these embodiments, the degree of graphitization of the third active material is higher than that of the second active material.
[0026] In some of these embodiments, the degree of graphitization of the first active material is 94% to 96%.
[0027] In some of these embodiments, the degree of graphitization of the second active material is 91% to 93%.
[0028] In some of these embodiments, the degree of graphitization of the third active material is 92% to 94%.
[0029] In some of these embodiments, the first negative electrode coating, the second negative electrode coating, and the third negative electrode coating all have a porous structure.
[0030] In some embodiments, the porosity of the third negative electrode coating is higher than that of the second negative electrode coating.
[0031] In some of these embodiments, the porosity of the first negative electrode coating is 25% to 35%.
[0032] In some of these embodiments, the porosity of the second negative electrode coating is 30% to 40%.
[0033] In some of these embodiments, the porosity of the third negative electrode coating is 35% to 45%.
[0034] In some of these embodiments, the first negative electrode coating includes a first adhesive, the second negative electrode coating includes a second adhesive, and the third negative electrode coating includes a third adhesive.
[0035] In some of these embodiments, the swelling rate of the third adhesive is higher than that of the second adhesive.
[0036] In some embodiments, the swelling rate of the first adhesive is 3% to 15%.
[0037] In some embodiments, the swelling rate of the second adhesive is 5% to 20%.
[0038] In some embodiments, the swelling rate of the third adhesive is 10% to 30%.
[0039] In some embodiments, the first active material includes at least one of artificial graphite, natural graphite, soft or hard carbon, or mesophase carbon microspheres.
[0040] In some of these embodiments, the average particle size Dv50 of the first active material is 10 μm to 18 μm, and Dv10 is 4 μm to 7 μm.
[0041] In some embodiments, the first negative electrode coating further includes a first conductive agent.
[0042] In some of these embodiments, the mass ratio of the first active material, the first conductive agent, and the first binder is (95-96):(2-5):(1-2).
[0043] In some of these embodiments, the thickness of the first negative electrode coating is 35 μm to 60 μm.
[0044] In some embodiments, the second active material includes at least one of artificial graphite, natural graphite, soft or hard carbon, or mesophase carbon microspheres.
[0045] In some embodiments, the average particle size Dv50 of the second active material is 10 μm to 15 μm, and Dv10 is 3.5 μm to 6.5 μm.
[0046] In some embodiments, the second negative electrode coating further includes a second conductive agent.
[0047] In some of these embodiments, the mass ratio of the second active material, the second conductive agent, and the second binder is (95-96):(2-5):(1-2).
[0048] In some embodiments, the thickness of the second negative electrode coating is 35 μm to 60 μm.
[0049] In some embodiments, the third active material includes at least one of artificial graphite or mesophase carbon microspheres.
[0050] In some embodiments, the average particle size Dv50 of the third active substance is 5 μm to 10 μm, and the average particle size Dv10 is ≥ 3 μm.
[0051] In some embodiments, the third negative electrode coating also includes a third conductive agent.
[0052] In some of these embodiments, the mass ratio of the third active material, the third conductive agent, and the third binder is (95-96):(2-5):(1-2).
[0053] In some of these embodiments, the thickness of the third negative electrode coating is 8 μm to 30 μm.
[0054] According to another aspect of this application, embodiments of this application provide a method for preparing a negative electrode sheet, comprising the following steps:
[0055] A first negative electrode slurry is coated on at least one side of the current collector to obtain a first negative electrode coating.
[0056] A second negative electrode slurry is coated on the surface of the first negative electrode coating to obtain a second negative electrode coating.
[0057] A third negative electrode slurry is coated onto the surface of the second negative electrode coating to obtain a third negative electrode coating.
[0058] The current collector coated with the first negative electrode coating, the second negative electrode coating, and the third negative electrode coating is subjected to roll drying.
[0059] The first negative electrode slurry includes a first active material, the second negative electrode slurry includes a second active material, and the third negative electrode slurry includes a third active material.
[0060] According to another aspect of this application, an embodiment of this application provides a battery including a negative electrode sheet, wherein the negative electrode sheet is the aforementioned negative electrode sheet or a negative electrode sheet prepared according to the aforementioned preparation method.
[0061] Implementing the technical solution of the present invention has at least the following beneficial effects:
[0062] In the negative electrode sheet of this application, the tap density of the first active material is T1, the tap density of the second active material is T2, and the tap density of the third active material is T3, wherein T3 > T1 > T2. The third active material uses a material with a higher tap density, resulting in a more rounded morphology and improving the high-temperature performance of the third negative electrode coating. The second active material uses a material with a lower tap density, ensuring the negative electrode sheet has higher fast-charging capability. The tap density of the first active material is higher than that of the second active material and lower than that of the third active material, allowing the first negative electrode coating to maintain high capacity and high tap density. By controlling the relationship between the tap densities of the active materials in the three-layer coating, the negative electrode sheet of this application allows the battery prepared from this negative electrode sheet to achieve both excellent fast-charging capability and high-temperature performance.
[0063] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Detailed Implementation
[0064] The present application will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.
[0065] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0066] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0067] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0068] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0069] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0070] In related technologies, a double-layer coating technique is used to improve the fast charging capability of batteries. However, because the negative electrode material with better fast charging capability is placed on the upper layer of the electrode sheet and in contact with the electrolyte, the high-temperature performance is degraded.
[0071] In view of this, embodiments of this application provide a negative electrode sheet, the negative electrode sheet comprising:
[0072] current collector;
[0073] A first negative electrode coating is disposed on at least one side surface of the current collector along the thickness direction. The first negative electrode coating includes a first active material, and the tap density of the first active material is T1.
[0074] A second negative electrode coating is disposed on the surface of the first negative electrode coating away from the current collector. The second negative electrode coating includes a second active material, the tap density of which is T2.
[0075] The third negative electrode coating is disposed on the surface of the second negative electrode coating that is away from the first negative electrode coating. The third negative electrode coating includes a third active material, and the tap density of the third active material is T3.
[0076] Among them, T1, T2, and T3 satisfy the following relationship:
[0077] T3 > T1 > T2.
[0078] The phrase "the first negative electrode coating is disposed on at least one surface of the current collector along its thickness direction" means that the first negative electrode coating can be disposed on one surface of the current collector along its own thickness direction, or it can be disposed on two surfaces of the current collector along its own thickness direction. Here, "surface" can be the entire area of the current collector or a part of the current collector. As in this embodiment, the surface can be the entire area of the current collector. This application does not have any particular limitation in this regard, as long as the purpose of this application can be achieved.
[0079] As an example, the current collector has two surfaces opposite each other in its thickness direction, and a first negative electrode coating is disposed on the two opposite surfaces of the current collector. Further, a second negative electrode coating is formed on both surfaces of the first negative electrode coating. Even further, a third negative electrode coating is formed on both surfaces of the second negative electrode coating. It is understood that in other embodiments, the first negative electrode coating may also be laminated on either of the two surfaces of the current collector.
[0080] In this application, the material of the current collector in the negative electrode is not specifically limited.
[0081] In the negative electrode sheet of this application, the tap density of the first active material is T1, the tap density of the second active material is T2, and the tap density of the third active material is T3, wherein T3 > T1 > T2. The third active material uses a material with a higher tap density, resulting in a more rounded morphology and improving the high-temperature performance of the third negative electrode coating. The second active material uses a material with a lower tap density, ensuring the negative electrode sheet has higher fast-charging capability. The tap density of the first active material is higher than that of the second active material and lower than that of the third active material, allowing the first negative electrode coating to maintain high capacity and high tap density. By controlling the relationship between the tap densities of the active materials in the three-layer coating, the negative electrode sheet of this application allows the battery prepared from this negative electrode sheet to achieve both excellent fast-charging capability and high-temperature performance.
[0082] As an example, the tap density of the material in the second active substance can be reduced by coating and / or granulation; the tap density of the material in the first active substance can be controlled by controlling the degree of coating and / or granulation and / or the proportion of the treated product.
[0083] This application does not limit the test method for the tap density of the material; for example, GB / T 21354-2008 (Test Method for Tap Density of Powder Products) can be used. The units for T1, T2, and T3 mentioned above are all g / cm³. 3 .
[0084] In some embodiments, the tap density T1 of the first active material satisfies: 1 g / cm³ 3≤T1≤1.2g / cm 3 As an example, the tap density T1 of the first active substance can be 1 g / cm³. 3 1.1g / cm 3 1.2g / cm 3 Of course, it could also be any point value within the above range, and no specific limitation is made here. Limiting the tap density T1 of the first active material to the above range allows the battery to achieve both high capacity and certain high-temperature performance.
[0085] In some embodiments, the tap density T2 of the second active material satisfies: 0.9 g / cm³ 3 ≤T1≤1.1g / cm 3 As an example, the tap density T1 of the second active material can be 0.9 g / cm³. 3 1g / cm 3 1.1g / cm 3 Of course, it can also be any point value within the above range, and no specific limitation is made here. Limiting the tap density T1 of the second active material within the above range can ensure the battery's fast charging capability.
[0086] In some embodiments, the tap density T3 of the third active material satisfies: T3 ≥ 1.1 g / cm³ 3 Preferably, T3 ≥ 1.2 g / cm³ 3 As an example, the tap density T1 of the third active material can be 0.9 g / cm³. 3 1g / cm 3 1.1g / cm 3 The value could be any point within the range mentioned above, and no specific limitation is made here. Limiting the tap density T1 of the third active material to the above range ensures that the battery has good high-temperature performance.
[0087] In some embodiments, the rate performance of the first active substance is C1, the rate performance of the second active substance is C2, and the rate performance of the third active substance is C3.
[0088] Among them, C1, C2, and C3 satisfy the following relationship:
[0089] 0.8*C2≤C3≤C2; The third active material has a certain rate performance. If C3 (the rate performance of the third active material) is lower than 0.8*C2, the overall fast-charging capability of the battery will decrease. Furthermore, the rate performance of the third active material cannot exceed that of the second active material; otherwise, the high-temperature performance of the battery will not be significantly improved. Specifically, the third active material layer is placed on the surface of the electrode near the separator, effectively isolating the surfaces of the first and second active material layers. Therefore, it must possess good high-temperature performance. Simultaneously, the lithium-ion concentration decreases in the order of the third, second, and first negative electrode coatings, requiring the third active material layer to have a certain fast-charging capability. The applicant discovered that when the rate performance of the third and second negative electrode coatings conforms to the above relationship, the decrease in the rate performance of the third active material does not significantly reduce the overall fast-charging capability of the battery, while simultaneously improving the high-temperature performance of the battery.
[0090] In some embodiments, C1 ≥ 0.5 * C3. The rate capability of the first active material is limited to this range, which can improve the fast charging capability at higher SOC levels in the later stages of lithium intercalation.
[0091] In this application, the rate performance of the first, second, and third active materials can be characterized using the 3C charging constant current ratio. Specifically, each active material is combined with carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and conductive carbon black SP in a ratio of 95:1.5:2:1.5 to assemble a coin cell with lithium foil. The cell is charged at a constant current of 0.1C to 0.005V, discharged at a constant current of 0.1C to 1.5V, then charged at a constant current of 3C to 0.005V, and discharged at a constant voltage of 0.05V. The charging constant current ratio is the ratio of the capacity of the constant current stage to the total capacity of the constant current and constant voltage stages.
[0092] In some embodiments, the OI value of the third active material layer is higher than that of the second active material layer. The third active material has better high-temperature performance, which can improve the overall high-temperature performance of the electrode.
[0093] In some embodiments, the OI value of the first active material layer is 20 to 30. As an example, the OI value of the first active material layer can be 20, 25, 30, etc., or it can be a value within the above range, and no specific limitation is made here.
[0094] In some embodiments, the OI value of the second active material layer is 5 to 20. As an example, the OI value of the second active material layer can be 5, 15, 20, etc., or it can be a value within the above range, and no specific limitation is made here.
[0095] In some embodiments, the OI value of the third active material layer is 15 to 25. As an example, the OI value of the third active material layer can be 15, 20, 25, etc., or it can be a value within the above range, and no specific limitation is made here.
[0096] In this application, the OI value refers to the graphite orientation degree, a parameter used to describe the degree of orderliness of the graphite sheet arrangement. It is generally calculated by measuring the intensity ratio of the diffraction peaks of the 002 and 110 crystal planes of graphite using an X-ray diffractometer (XRD).
[0097] In some embodiments, the graphitization degree of the third active material is higher than that of the second active material. This improves the high-temperature performance of the third negative electrode coating, thereby enhancing the overall high-temperature performance of the battery.
[0098] In some embodiments, the graphitization degree of the first active material is 94% to 96%. As an example, the graphitization degree of the first active material can be 94%, 95%, 96%, etc., or it can be a value within the above range, without being specifically limited here.
[0099] In some embodiments, the degree of graphitization of the second active material is 91% to 93%. As an example, the degree of graphitization of the second active material can be 91%, 92%, 93%, etc., or it can be a value within the above range, without being specifically limited here.
[0100] In some embodiments, the graphitization degree of the third active material is 92% to 94%. As an example, the graphitization degree of the third active material can be 92%, 93%, 94%, etc., or it can be a value within the above range, without being specifically limited here.
[0101] It should be noted that the graphitization degree of the first active material, the graphitization degree of the second active material, and the graphitization degree of the third active material can also be replaced by the average graphitization degree of the first negative electrode coating, the average graphitization degree of the second negative electrode coating, and the average graphitization degree of the third negative electrode coating. The relationship between the average graphitization degree of the first negative electrode coating, the average graphitization degree of the second negative electrode coating, and the average graphitization degree of the third negative electrode coating follows the magnitude relationship and value range of the graphitization degree of the first active material, the second active material, and the third active material.
[0102] Graphitization degree is an indicator of how closely the crystal structure of carbon materials (such as graphite) approximates the ideal graphite crystal. Ideal graphite has a close-packed hexagonal crystal structure, while in actual materials, lattice parameters deviate from ideal values due to manufacturing processes or defects. Graphitization degree is determined by measuring the diffraction peaks of the 002 crystal plane of graphite using X-ray diffraction (XRD), then calculating the interlayer spacing d002 of graphite using the Bragg equation, and finally comparing it with the interlayer spacing of ideal graphite.
[0103] In some embodiments, the first negative electrode coating, the second negative electrode coating, and the third negative electrode coating all have a porous structure.
[0104] In some embodiments, the porosity of the third negative electrode coating is higher than that of the second negative electrode coating. This improves the ion transport capability of the third negative electrode coating and enhances the battery's fast-charging performance.
[0105] In some embodiments, the porosity of the first negative electrode coating is 25% to 35%. As an example, the porosity of the first negative electrode coating can be 25%, 30%, 35%, etc., or it can be a value within the above range, without being specifically limited here.
[0106] In some embodiments, the porosity of the second negative electrode coating is 30% to 40%. As an example, the porosity of the second negative electrode coating can be 25%, 30%, 35%, etc., or it can be a value within the above range, without being specifically limited here.
[0107] In some embodiments, the porosity of the third negative electrode coating is 35% to 45%. As an example, the porosity of the third negative electrode coating can be 25%, 30%, 35%, etc., or it can be a value within the above range, without being specifically limited here.
[0108] Porosity refers to the percentage of the internal pore volume in the negative electrode coating to the total volume of the coating, and is used to measure the distribution ratio of pores in the coating. The test method for coating porosity includes: after drying the electrode, soaking it in n-hexadecane until all the pores of the electrode are filled, then using lint-free paper to absorb the excess hexadecane on the surface, weighing it, and calculating the porosity of the coating.
[0109] In some embodiments, the first negative electrode coating includes a first adhesive, the second negative electrode coating includes a second adhesive, and the third negative electrode coating includes a third adhesive.
[0110] In some embodiments, the first adhesive, the second adhesive, and the third adhesive each independently include at least one of polyacrylic acid, polyacrylate, or styrene-butadiene rubber. As an example, it can be polyacrylic acid or polyacrylate.
[0111] In some embodiments, the swelling ratio of the third binder is higher than that of the second binder. Thus, the higher swelling ratio of the third binder creates more porosity, increasing the fast-charging capability of the third negative electrode coating.
[0112] In some embodiments, the swelling rate of the first adhesive is 3% to 15%. As an example, the swelling rate of the first adhesive can be 3%, 8%, 10%, 15%, etc., or it can be a value within the above range, without being specifically limited here.
[0113] In some embodiments, the swelling rate of the second adhesive is 5% to 20%. As an example, the swelling rate of the second adhesive can be 5%, 10%, 15%, 20%, etc., or it can be a value within the above range, without being specifically limited here.
[0114] In some embodiments, the swelling rate of the third adhesive is 10% to 30%. As an example, the swelling rate of the third adhesive can be 10%, 15%, 25%, 30%, etc., or it can be a value within the above range, without being specifically limited here.
[0115] In this application, the swelling rates of the first, second, and third adhesives refer to the swelling rates after soaking in an electrolyte solution obtained by mixing ethylene carbonate, methyl ethyl carbonate, and diethyl carbonate in a mass ratio of 1:1:1 for 24 hours.
[0116] In some embodiments, the first active material includes, but is not limited to, at least one of artificial graphite, natural graphite, soft or hard carbon, or mesophase carbon microspheres. As an example, the first active material may be artificial graphite, natural graphite, or a mixture of both.
[0117] In some embodiments, the average particle size Dv50 of the first active material is 10 μm to 18 μm, and Dv10 is 4 μm to 7 μm. As an example, the average particle size Dv50 of the first active material can be 10 μm, 14 μm, 18 μm, etc., or any value within the above range; no specific limitation is made here. The average particle size Dv10 of the first active material can be 4 μm, 5 μm, 7 μm, etc., or any value within the above range; no specific limitation is made here. Limiting the average particle sizes Dv50 and Dv10 of the first active material to the above range allows the first active material to have higher capacity and compaction, thereby improving the energy density of the finished negative electrode sheet.
[0118] In some embodiments, the first negative electrode coating also includes a first conductive agent.
[0119] In some embodiments, the mass ratio of the first active material, the first conductive agent, and the first binder is (95-96):(2-5):(1-2). As an example, the mass ratio of the first active material, the first conductive agent, and the first binder can be 95:2:1, 95.5:3.5:1.5, 96:5:2, etc., or any ratio within the above range, without specific limitation here.
[0120] In some embodiments, the thickness of the first negative electrode coating is 35 μm to 60 μm. As an example, the thickness of the first negative electrode coating can be 35 μm, 45 μm, 55 μm, 60 μm, etc., or it can be a value within the above range, and no specific limitation is made here.
[0121] In some embodiments, the second active material includes, but is not limited to, at least one of artificial graphite, natural graphite, soft or hard carbon, or mesophase carbon microspheres. As an example, the second active material may be artificial graphite, natural graphite, or a mixture of both.
[0122] In some embodiments, the average particle size Dv50 of the second active material is 10 μm to 15 μm, and Dv10 is 3.5 μm to 6.5 μm. As an example, the average particle size Dv50 of the second active material can be 10 μm, 14 μm, 15 μm, etc., or any value within the above range; no specific limitation is made here. The average particle size Dv10 of the second active material can be 3.5 μm, 5 μm, 6.5 μm, etc., or any value within the above range; no specific limitation is made here. Limiting the average particle sizes Dv50 and Dv10 of the second active material to the above range can improve the fast-charging capability of the second negative electrode coating.
[0123] In some embodiments, the second negative electrode coating also includes a second conductive agent.
[0124] In some embodiments, the mass ratio of the second active material, the second conductive agent, and the second binder is (95-96):(2-5):(1-2). As an example, the mass ratio of the second active material, the second conductive agent, and the second binder can be 95:2:1, 95.5:3.5:1.5, 96:5:2, etc., or any ratio within the above range, without specific limitation.
[0125] In some embodiments, the thickness of the second negative electrode coating is 35 μm to 60 μm. As an example, the thickness of the second negative electrode coating can be 35 μm, 45 μm, 55 μm, 60 μm, etc., or it can be any value within the above range, and no specific limitation is made here.
[0126] In some embodiments, the third active material includes, but is not limited to, at least one of artificial graphite or mesophase carbon microspheres. As an example, the third active material may be artificial graphite, mesophase carbon microspheres, or a mixture of both.
[0127] In some embodiments, the average particle size Dv50 of the third active material is 5 μm to 10 μm, and the average particle size Dv10 is ≥ 3 μm. As an example, the average particle size Dv50 of the third active material can be 5 μm, 8 μm, 10 μm, etc., or any value within the above range; no specific limitation is made here. The average particle size Dv10 of the third active material can be 3 μm, 4 μm, 5 μm, etc., or any value within the above range; no specific limitation is made here. The relatively small particle size of the third active material results in low ion migration tortuosity, which can balance the fast charging capability of the battery; and controlling the content of medium and fine powder in the third active material can further improve high-temperature performance.
[0128] In some embodiments, the third negative electrode coating also includes a third conductive agent.
[0129] In some embodiments, the mass ratio of the third active material, the third conductive agent, and the third binder is (95-96):(2-5):(1-2). As an example, the mass ratio of the third active material, the third conductive agent, and the third binder can be 95:2:1, 95.5:3.5:1.5, 96:5:2, etc., or any ratio within the above range, without specific limitation.
[0130] In some embodiments, the thickness of the third negative electrode coating is 8 μm to 30 μm. As an example, the thickness of the second negative electrode coating can be 8 μm, 15 μm, 25 μm, 30 μm, etc., or any value within the above range; no specific limitation is made here. If the thickness of the third negative electrode coating is too thick, it affects lithium-ion transport and reduces lithium-ion throughput efficiency; if the thickness of the third negative electrode coating is too low, the processing is difficult, the electrolyte isolation effect is poor, and the high-temperature performance improvement is not significant; limiting the thickness of the third negative electrode coating within the above range results in the best overall performance.
[0131] It should be noted that the first conductive agent, the second conductive agent, and the third conductive agent each independently include, but are not limited to, at least one of conductive graphite, conductive carbon black, conductive carbon fiber, carbon nanotubes, or graphene. The aforementioned conductive carbon black includes acetylene black, Ketjen black, etc. The aforementioned conductive carbon fiber includes vapor-grown carbon fiber.
[0132] It is understandable that the mass ratios of the first active material, the first conductive agent, and the first binder; the mass ratios of the second active material, the second conductive agent, and the second binder; and the mass ratios of the third active material, the third conductive agent, and the third binder are related to the electrochemical performance of the corresponding battery and further affect the structural stability of the negative electrode sheet. By controlling the proportions of each substance in the first, second, and third negative electrode coatings within the aforementioned ranges, the interaction between the materials is fully utilized, effectively improving the cycle performance, fast-charging performance, and high-temperature performance of the negative electrode sheet.
[0133] It is also understandable that the thickness of the coating affects the battery's electrical performance (such as energy density, cycle performance, and rate performance), manufacturing cost, and safety performance. If the thickness of the first, second, and third negative electrode coatings is too large, the electron transport distance increases, electronic resistance increases, and rate performance decreases, adversely affecting the battery's electrical performance and further increasing the difficulty of thermal management. However, if the thickness of the first, second, and third negative electrode coatings is too small, the improvement on the structural stability of the positive electrode is not significant, which will adversely affect the battery's safety and long-term cycle stability.
[0134] Therefore, based on the above scheme, the tap density of the first active material is T1, the tap density of the second active material is T2, and the tap density of the third active material is T3, where T3 > T1 > T2. The third active material uses a material with a higher tap density, resulting in a more rounded morphology, which improves the high-temperature performance of the third negative electrode coating. The second active material uses a material with a lower tap density, ensuring the negative electrode sheet has higher fast-charging capability. The tap density of the first active material is higher than that of the second active material and lower than that of the third active material, allowing the first negative electrode coating to maintain high capacity and high tap density. By controlling the relationship between the tap densities of the active materials in the three-layer coating, the negative electrode sheet of this application can enable the battery prepared from this negative electrode sheet to achieve both excellent fast-charging capability and high-temperature performance.
[0135] Furthermore, the third active material is limited to a certain rate performance. If C3 (the rate performance of the third active material) is lower than 0.8*C2 (C2 being the rate performance of the second active material), the overall fast-charging capability of the battery will decrease. Moreover, the rate performance of the third active material cannot exceed that of the second active material; otherwise, the battery's high-temperature performance will not be significantly improved. By setting the particle size of the third active material to be relatively small, resulting in low ion migration tortuosity, the battery's fast-charging capability can be balanced. Controlling the content of medium and fine powder in the third active material can further improve the battery's high-temperature performance. The thickness of the third negative electrode coating is also further controlled, ensuring that the third negative electrode coating has both high ion transport efficiency and good high-temperature performance.
[0136] According to another aspect of this application, embodiments of this application provide a method for preparing a negative electrode sheet, comprising the following steps:
[0137] A first negative electrode slurry is coated on at least one side of the current collector to obtain a first negative electrode coating.
[0138] A second negative electrode slurry is coated on the surface of the first negative electrode coating to obtain a second negative electrode coating.
[0139] A third negative electrode slurry is coated onto the surface of the second negative electrode coating to obtain a third negative electrode coating.
[0140] The current collector coated with the first negative electrode coating, the second negative electrode coating, and the third negative electrode coating is subjected to roll drying.
[0141] The first negative electrode slurry includes a first active material, the second negative electrode slurry includes a second active material, and the third negative electrode slurry includes a third active material.
[0142] It should be understood that all the features and advantages described above regarding the "negative electrode sheet" also apply to the "preparation method of the negative electrode sheet," and will not be repeated here.
[0143] In some specific embodiments, the preparation method of the negative electrode sheet specifically includes steps S1 to S6:
[0144] S1 prepares the first negative electrode slurry.
[0145] In step S1, the preparation of the first negative electrode slurry includes: mixing the first active material, the first conductive agent and the first binder evenly in a solvent to obtain the first negative electrode slurry.
[0146] In some embodiments, the solvent includes water.
[0147] S2 is used to prepare the second negative electrode slurry.
[0148] In step S2, the preparation of the second negative electrode slurry includes: mixing the second active material, the second conductive agent, and the second binder uniformly in a solvent to obtain the second negative electrode slurry.
[0149] In some embodiments, the solvent includes water.
[0150] S3 is used to prepare the third negative electrode slurry.
[0151] In step S3, the preparation of the third negative electrode slurry includes: mixing the third active material, the third conductive agent and the third binder evenly in a solvent to obtain the second negative electrode slurry.
[0152] In some embodiments, the solvent includes water.
[0153] S4 coating.
[0154] In step S4, the first negative electrode slurry is coated onto the surface of the current collector and dried to complete the coating of the first negative electrode; the second negative electrode slurry is coated onto the surface of the first negative electrode coating and dried to complete the coating of the second negative electrode; the third negative electrode slurry is coated onto the surface of the second negative electrode coating and dried to complete the coating of the third negative electrode.
[0155] S5 roller pressing.
[0156] In step S4, the three-layer coated electrode sheet is rolled to the target compaction density. The compaction density of the embodiment and the comparative example is 1.65 g / cm³. 3 .
[0157] Based on the above scheme, the tap density of the first active material is T1, the tap density of the second active material is T2, and the tap density of the third active material is T3, where T3 > T1 > T2. The third active material uses a material with a higher tap density, resulting in a more rounded morphology, which improves the high-temperature performance of the third negative electrode coating. The second active material uses a material with a lower tap density, ensuring the negative electrode sheet has higher fast-charging capability. The tap density of the first active material is higher than that of the second active material and lower than that of the third active material, allowing the first negative electrode coating to maintain high capacity and high tap density. By controlling the relationship between the tap densities of the active materials in the three-layer coating, the negative electrode sheet of this application allows the battery prepared from this negative electrode sheet to achieve both excellent fast-charging capability and high-temperature performance.
[0158] Furthermore, the third active material is limited to a certain rate performance. If C3 (the rate performance of the third active material) is lower than 0.8*C2 (C2 being the rate performance of the second active material), the overall fast-charging capability of the battery will decrease. Moreover, the rate performance of the third active material cannot exceed that of the second active material; otherwise, the battery's high-temperature performance will not be significantly improved. By setting the particle size of the third active material to be relatively small, resulting in low ion migration tortuosity, the battery's fast-charging capability can be balanced. Controlling the content of medium and fine powder in the third active material can further improve the battery's high-temperature performance. The thickness of the third negative electrode coating is also further controlled, ensuring that the third negative electrode coating has both high ion transport efficiency and good high-temperature performance.
[0159] Based on the same inventive concept, this application provides a battery including a negative electrode sheet, which includes the aforementioned negative electrode sheet or a negative electrode sheet prepared according to the aforementioned preparation method.
[0160] Because this battery includes the negative electrode provided in the embodiments of this application, it has superior fast charging performance and high-temperature performance.
[0161] In some embodiments, the battery may be a lithium-ion battery. The battery stacking type may be, for example, a wound or stacked battery, and the structural type may be, for example, a prismatic (aluminum, steel, etc.) battery, a pouch battery, or a cylindrical battery, etc., and there is no specific limitation.
[0162] In some embodiments, the battery further includes a positive electrode, an electrolyte, and a separator. That is, the battery includes a positive electrode, a negative electrode, an electrolyte, and a separator.
[0163] In this embodiment, the materials and structures of the positive electrode current collector, the conductive agent and the binder in the positive electrode active material layer are not limited, and the positive electrode structure and composition known in the art that can be used in secondary batteries can be selected.
[0164] In this embodiment, the specific material or type of the separator is not limited, and any separator known in the art that can be used in secondary batteries can be selected.
[0165] It should also be noted that the battery in this application does not limit the specific material or type of electrolyte. Any components and types known in the art that can be used in secondary batteries can be selected, as long as the purpose of this application can be achieved.
[0166] Since the battery provided in this embodiment of the invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, and will not be described in detail here.
[0167] The following describes the implementation methods of this application. The implementation methods described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the implementation methods, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents, materials, or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0168] Example 1
[0169] Preparation of the first negative electrode slurry: The first active material, artificial graphite, carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and conductive carbon black (Super-P) are placed in a stirred tank in a ratio of 95.5:1.5:2:1. After adding pure water and stirring evenly, the first negative electrode slurry is obtained.
[0170] The first active material, artificial graphite, has a tap density of 1.05 g / cm³. 3 The ratio performance is 83%, the OI value is 24.4, the degree of graphitization is 95.1%, the average particle size Dv50 is 15.3 μm, the average particle size Dv10 is 5.7 μm, and the swelling rate of the selected carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) is 8.4%.
[0171] Preparation of the second negative electrode slurry: The second active material, artificial graphite, carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and conductive carbon black (Super-P) are placed in a stirred tank in a ratio of 95.5:1.5:2:1. After adding pure water and stirring evenly, the second negative electrode slurry is obtained.
[0172] The second active material, artificial graphite, has a tap density of 0.99 g / cm³.3 The ratio performance is 97%, the OI value is 11.0, the degree of graphitization is 92.3, the average particle size Dv50 is 13.5um, the average particle size Dv10 is 5.6um, and the swelling ratio of the selected carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) is 12.5.
[0173] Preparation of the third negative electrode slurry: The third active material, artificial graphite, carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and conductive carbon black (Super-P) are placed in a stirred tank in a ratio of 95.5:1.5:2:1. After adding pure water and stirring evenly, the third negative electrode slurry is obtained.
[0174] The third active material, artificial graphite, has a tap density of 1.21 g / cm³. 3 The ratio performance is 93%, the OI value is 23.4, the degree of graphitization is 92.7%, the average particle size Dv50 is 8.5μm, the average particle size Dv10 is 4.0μm, and the swelling rate of the selected carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) is 18.7%.
[0175] Coating slurry: The first negative electrode slurry is coated onto the surface of the current collector and dried to complete the first negative electrode coating; the second negative electrode slurry is coated onto the surface of the first negative electrode coating and dried to complete the second negative electrode coating; the third negative electrode slurry is coated onto the surface of the second negative electrode coating and dried to complete the third negative electrode coating.
[0176] The thickness of the first negative electrode coating is 45 μm, the thickness of the second negative electrode coating is 45 μm, and the thickness of the third negative electrode coating is 15 μm.
[0177] Example 2
[0178] The difference between Example 2 and Example 1 is that the tap density of the first active material, artificial graphite, is 1.18 g / cm³. 3 The tap density of the third active material, artificial graphite, is 1.23 g / cm³. 3 The average particle size of the third active material, artificial graphite, is 9.3 μm (Dv50) and 4.4 μm (Dv10), and the binder swelling is 28.4%.
[0179] Example 3
[0180] The difference between Example 3 and Example 2 is that the tap density of the second active material, artificial graphite, is 1.09 g / cm³. 3 .
[0181] Example 4
[0182] The difference between Example 4 and Example 1 is that the tap density of the third active material, artificial graphite, is 1.23 g / cm³. 3 .
[0183] Example 5
[0184] The difference between Example 5 and Example 1 is that the tap density of the third active material, artificial graphite, is 1.19 g / cm³. 3 The average particle size of the third active material, artificial graphite, is 5.2 μm for Dv50 and 3.3 μm for Dv10.
[0185] Example 6
[0186] The difference between Example 6 and Example 1 is that the thickness of the third negative electrode coating is 25 μm, while the thickness of the first and second negative electrode coatings is 40 μm.
[0187] Example 7
[0188] The difference between Example 7 and Example 1 is that the first active material, artificial graphite, has a rate capability of 50%, a particle size Dv50 of 17.6 μm, a Dv10 of 6.8 μm, the third active material, artificial graphite, has a rate capability of 79%, and the binder swelling is 10.2%.
[0189] Example 8
[0190] The difference between Example 8 and Example 1 is that the first active material, artificial graphite, has an OI value of 21.1 and a rate performance of 85%, the second active material, artificial graphite, has an OI value of 5.8 and a rate performance of 99%, and the third active material, artificial graphite, has an OI value of 16.2 and a rate performance of 96%.
[0191] Example 9
[0192] The difference between Example 9 and Example 1 is that the average particle size Dv50 of the first active material artificial graphite is 10.3 μm, the average particle size Dv10 is 4.1 μm, and the rate performance is 90%, while the average particle size Dv50 of the second active material artificial graphite is 10.2 μm, the average particle size Dv10 is 3.7 μm, and the rate performance is 99%.
[0193] Example 10
[0194] The difference between Example 10 and Example 1 is that the swelling rate of carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) used in the first negative electrode coating is 14.6% and the degree of graphitization is 95.5%, while the swelling rate of carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) used in the second negative electrode coating is 5.3% and the degree of graphitization is 91.8%.
[0195] Comparative Example 1
[0196] The difference between Comparative Example 1 and Example 1 is that the tap density of the first active material, artificial graphite, is 0.98 g / cm³. 3 .
[0197] Comparative Example 2
[0198] The difference between Comparative Example 2 and Example 1 is that the tap density of the second active material, artificial graphite, is 1.09 g / cm³. 3 .
[0199] Battery fabrication and performance testing
[0200] 1. Battery manufacturing
[0201] Preparation of positive electrode sheet: Lithium iron phosphate, polyvinylidene fluoride (PVDF) and conductive carbon black (Super-P) are mixed in a ratio of 97:2:1 and stirred to form a positive electrode slurry. The positive electrode slurry is coated on aluminum foil (thickness**), dried in an oven, and then rolled and slit to obtain the positive electrode sheet.
[0202] Separator: A polyethylene (PE) membrane with a thickness of 12μm is selected as the separator.
[0203] Electrolyte: Ethyl carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent at a ratio of 1.2 mol / L to prepare the electrolyte.
[0204] Full cell preparation: The positive electrode sheet, separator, and negative electrode sheet from the above embodiments and comparative examples are arranged in sequence. A separator layer is placed between each pair of positive and negative electrodes, and the cells are wound to obtain a bare cell. The bare cell is placed in an outer packaging shell, and the prepared electrolyte is injected into the dried bare cell. After vacuum sealing, settling, formation, and shaping, a lithium-ion battery is obtained.
[0205] 2. Compaction test of 20T pressure electrode sheet
[0206] The electrode sheet was pressed under a fixed pressure of 20T roller press, and the thickness of the electrode sheet after rolling was tested. The actual compaction density value was calculated based on the density before rolling and the thickness of the electrode sheet after rolling.
[0207] 3. 45℃ Cyclic Life Test
[0208] ① Place the battery in a 25℃ incubator for 6 hours;
[0209] ② First, charge at a constant current of 0.33C to 3.65V, then charge at a constant voltage of 3.65V to 0.05C, and let stand for 10 minutes;
[0210] ③ Discharge at a constant current of 0.33C to 2.5V, and let stand for 10 minutes;
[0211] ④ Repeat the cycle 3 times, and record the discharge capacity of the last cycle as C0;
[0212] ⑤ Remove the battery from the 25℃ incubator and place it in a 45℃ incubator for 6 hours;
[0213] ⑥ Charge at 1C0 constant current to 3.65V, then charge at 3.65V constant voltage to 0.05C, and let stand for 10 minutes;
[0214] ⑦ Discharge 1C0 at a constant current to 2.5V and let it stand for 10 minutes;
[0215] ⑧ Record and mark the discharge capacity of each cycle during the cycle, for example, the capacity of the first cycle is C1, and the capacity of the nth cycle is Cn; the SOH of the battery in the nth cycle is calculated as: Cn / C1*100%; record the number of cycles when the battery reaches 80% SOH, which is the high temperature cycle life of the battery.
[0216] 4. Charging capability test (4C fast charging test to check lithium plating)
[0217] ① Place the battery in a 25℃ incubator for 6 hours;
[0218] ② First, charge at a constant current of 0.33C to 3.65V, then charge at a constant voltage of 3.65V to 0.05C, and let stand for 10 minutes;
[0219] ③ Discharge at a constant current of 0.33C to 2.5V, and let stand for 10 minutes;
[0220] ④ Repeat the cycle 3 times, and record the discharge capacity of the last cycle as C0;
[0221] ⑤ First charge with 4C0 constant current to 3.65V, then charge with 3.65V constant voltage to 0.05C, and let stand for 10 minutes;
[0222] ⑥ Discharge 4C0 at a constant current to 2.5V and let it stand for 10 minutes;
[0223] ⑦ After 50 cycles, remove the battery and disassemble it to observe the lithium plating at the negative electrode interface.
[0224] The test results are shown in Table 1.
[0225] Table 1
[0226]
[0227] Examples 2, 3, and 4, by increasing the tap density, resulted in more rounded particle morphology, which is beneficial for improving compaction and high-temperature life. Example 5, by reducing the tap density, slightly deteriorated compaction and high-temperature life, but the difference was not significant. Example 6, by increasing the thickness of the third active layer and reducing the contact between the electrolyte and the first and second active layers, significantly improved cycle life, and the reduction in electrode compaction was not obvious. Example 7, by reducing the ratio of the first and third active layers, improved compaction and cycle life, and the deterioration of kinetic performance was within an acceptable range. Example 8, by reducing the electrode OI value, did not significantly deteriorate compaction and cycle life. Example 9, by reducing the particle size of the first and third active materials, slightly reduced compaction and cycle life. Example 10, by increasing the first active layer and reducing the graphitization degree of the second active layer, maintained relatively similar overall performance.
[0228] Comparative Example 1 resulted in the tap density of the first active material exceeding that of the third active layer. In order to obtain an ultra-high tap density, the capacity and compaction of the material were significantly reduced, which in turn severely reduced the compaction density of the electrode.
[0229] Comparative Example 2 shows that the tap density of the second active material exceeds that of the first active layer. The increase in the tap density of the second active material leads to a decrease in dynamic performance, which in turn severely affects the battery's fast charging capability.
[0230] The parts of this invention not described in detail are techniques known to those skilled in the art.
[0231] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.
[0232] It should be noted that the terms "and / or" or " / " used herein are merely descriptions of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. The singular forms "a," "described," and "the" used in the embodiments of the invention and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.
[0233] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.
[0234] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A negative electrode sheet, characterized in that, The negative electrode includes: current collector; A first negative electrode coating is disposed on at least one side surface of the current collector along the thickness direction. The first negative electrode coating includes a first active material, and the tap density of the first active material is T1. A second negative electrode coating is disposed on the surface of the first negative electrode coating away from the current collector. The second negative electrode coating includes a second active material, the tap density of which is T2. A third negative electrode coating is disposed on the surface of the second negative electrode coating away from the first negative electrode coating. The third negative electrode coating includes a third active material, and the tap density of the third active material is T3. Among them, T1, T2, and T3 satisfy the following relationship: T3 > T1 > T2; The rate performance of the first active substance is C1, the rate performance of the second active substance is C2, and the rate performance of the third active substance is C3. Among them, C1, C2, and C3 satisfy the following relationship: 0.8 C2≤C3≤C2; C1≥0.5 C3; The first active material includes at least one of artificial graphite, natural graphite, soft or hard carbon, or mesophase carbon microspheres; The second active material includes at least one of artificial graphite, natural graphite, soft or hard carbon, or mesophase carbon microspheres; The third active material includes at least one of artificial graphite or mesophase carbon microspheres.
2. The negative electrode sheet according to claim 1, characterized in that, The tap density T1 of the first active substance satisfies: 1 g / cm³ 3 ≤T1≤1.2g / cm 3 ; And / or, the tap density T2 of the second active material satisfies: 0.9 g / cm³ 3 ≤T1≤1.1g / cm 3 ; And / or, the tap density T3 of the third active substance satisfies: T3 ≥ 1.1 g / cm³ 3 .
3. The negative electrode sheet according to claim 2, characterized in that, The tap density T3 of the third active material satisfies: T3 ≥ 1.2 g / cm³ 3 .
4. The negative electrode sheet according to claim 1, characterized in that, The first active substance, the second active substance, and the third active substance satisfy at least one of the following characteristics (1) to (2): (1) The OI value of the third active material layer is higher than that of the second active material layer; The OI value of the first active material layer is 20~30; The OI value of the second active material layer is 5~20; The OI value of the third active material layer is 15~25; (2) The degree of graphitization of the third active material is higher than that of the second active material; The graphitization degree of the first active material is 94%~96%; The graphitization degree of the second active material is 91%~93%; The graphitization degree of the third active material is 92%~94%.
5. The negative electrode sheet according to claim 1, characterized in that, The first negative electrode coating, the second negative electrode coating, and the third negative electrode coating satisfy at least one of the following characteristics (1) to (2): (1) The first negative electrode coating, the second negative electrode coating, and the third negative electrode coating all have a porous structure; The porosity of the third negative electrode coating is higher than that of the second negative electrode coating; The porosity of the first negative electrode coating is 25%~35%; The porosity of the second negative electrode coating is 30%~40%; The porosity of the third negative electrode coating is 35%~45%; (2) The first negative electrode coating includes a first adhesive, the second negative electrode coating includes a second adhesive, and the third negative electrode coating includes a third adhesive; The swelling rate of the third adhesive is higher than that of the second adhesive; The swelling rate of the first adhesive is 3%~15%; The swelling rate of the second adhesive is 5%~20%; The swelling rate of the third adhesive is 10% to 30%.
6. The negative electrode sheet according to claim 1, characterized in that, The first negative electrode coating satisfies at least one of the following features (1) to (3): (1) The average particle size Dv50 of the first active substance is 10 μm to 18 μm, and Dv10 is 4 μm to 7 μm; (2) The first negative electrode coating also includes a first conductive agent; The mass ratio of the first active material, the first conductive agent, and the first binder is (95~96):(2~5):(1~2); (3) The thickness of the first negative electrode coating is 35μm ~60μm.
7. The negative electrode sheet according to claim 1, characterized in that, The second negative electrode coating satisfies at least one of the following features (1) to (3): (1) The average particle size Dv50 of the second active substance is 10 μm to 15 μm, and Dv10 is 3.5 μm to 6.5 μm; (2) The second negative electrode coating also includes a second conductive agent; The mass ratio of the second active material, the second conductive agent, and the second binder is (95~96):(2~5):(1~2); (3) The thickness of the second negative electrode coating is 35μm ~60μm.
8. The negative electrode sheet according to claim 1, characterized in that, The third negative electrode coating satisfies at least one of the following characteristics (1) to (3): (1) The average particle size Dv50 of the third active substance is 5μm~10μm, and the average particle size Dv10 is ≥3μm; (2) The third negative electrode coating also includes a third conductive agent; The mass ratio of the third active material, the third conductive agent and the third binder is (95~96):(2~5):(1~2); (3) The thickness of the third negative electrode coating is 8μm ~ 30μm.
9. The method for preparing the negative electrode sheet according to any one of claims 1 to 8, characterized in that, Includes the following steps: A first negative electrode slurry is coated on at least one side of the current collector to obtain a first negative electrode coating. A second negative electrode slurry is coated on the surface of the first negative electrode coating to obtain a second negative electrode coating. A third negative electrode slurry is coated onto the surface of the second negative electrode coating to obtain a third negative electrode coating. The current collector coated with the first negative electrode coating, the second negative electrode coating, and the third negative electrode coating is subjected to roll drying. The first negative electrode slurry includes a first active material, the second negative electrode slurry includes a second active material, and the third negative electrode slurry includes a third active material.
10. A battery, comprising a negative electrode, characterized in that, The negative electrode sheet includes the negative electrode sheet according to any one of claims 1 to 8, or includes the negative electrode sheet prepared by the preparation method according to claim 9.
Citation Information
Patent Citations
Negative pole piece and preparation method thereof, and fast-charging lithium ion battery
CN119314992A
Negative plate and secondary battery
CN221427780U